The Juridical Implementation of Regional Regulation Number 11 of 2023 Regarding Local Taxes and Levies on the Elimination of Subscription Parking in Tulungagung - Setianingsih, Linda; Purnomo, Bagus Setiyo (Westscience Press, 2024)
The implementation of Regional Regulation Number 11 of 2023 concerning Local Taxes and Levies in Tulungagung District has significantly altered the management of public parking services. This regulation abolishes the subscription parking system and replaces it with a conventional ticket sales system. The accompanying procedural and technical changes aim to streamline operations and enhance revenue collection for the local government. This study investigates the juridical-sociological aspects of the implementation process, focusing on its impacts on local revenue, quality of public services, and citizen satisfaction. Through qualitative analysis involving primary data from interviews and secondary data from documentation and field observations, the research evaluates how the elimination of subscription parking has affected revenue generation and service provision. Key findings highlight a significant decline in revenue from subscription parking but indicate potential benefits in improving service efficiency and citizen satisfaction. Recommendations include continuous policy evaluation and adaptation to optimize regional financial management and public service provision in Tulungagung District.